2005
DOI: 10.2527/2005.83112501x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor expression in skeletal muscle and adipose tissue in response to in vivo porcine somatotropin treatment1,2

Abstract: The present study was performed to examine the response of leptin and leptin receptor (Rb) genes to porcine somatotropin (pST) stimuli in finishing pigs. Twelve crossbred barrows (Yorkshire x Landrace) were used in this study. Animals were individually fed a basal diet containing 18% CP, 1.2% lysine, and 3.5 Mcal of DE/kg ad libitum (as-fed basis). At 90 kg, six pigs were treated with daily injections of recombinant pST (10 mg) in sterile bicarbonate buffer, whereas the other six pigs were injected with steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…As in mammals, birds, and medaka (Frühbeck et al, 1999; Richards and Poch, 2003; Ramsay and Richards; 2005; Solberg et al, 2005; Guerra et al, 2007, Wong et al 2007), zebrafish skeletal (trunk) muscles express lepr . Interestingly, the highest lepr expression levels in the trunk muscles, judging from staining intensity, were detected in three day old zebrafish.…”
Section: Discussionmentioning
confidence: 98%
“…As in mammals, birds, and medaka (Frühbeck et al, 1999; Richards and Poch, 2003; Ramsay and Richards; 2005; Solberg et al, 2005; Guerra et al, 2007, Wong et al 2007), zebrafish skeletal (trunk) muscles express lepr . Interestingly, the highest lepr expression levels in the trunk muscles, judging from staining intensity, were detected in three day old zebrafish.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research has shown that in humans, rats and mice, the hormones leptin, ghrelin and obestatin are expressed in skeletal muscles (Gurriarán‐Rodríguez et al, , ; Hamrick et al, ; Margetic, Gazzola, Pegg, & Hill, ; Ramsay & Richards, ; Santos‐Zas et al, ; Solberg et al, ; Sugiyama et al, ; Togliatto et al, ). Two hypotheses have been suggested for the expression of these hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, a 167 amino acid polypeptide, is the product of the ob gene, which is expressed primarily in adipose tissues although recent studies have confirmed the expression of leptin in a variety of other tissues, including placenta [1], mammary tissue [2], fetal cartilage [3], skeletal muscle [4] stomach [5], cardiomyocytes [6] and vascular smooth muscle [7]. As a regulatory hormone, the first described major action of leptin was on the hypothalamus regulating appetite and weight in both humans and rodents.…”
Section: Leptin Biologymentioning
confidence: 99%